Analisis Metode Pendidikan Islam Dalam Sudut Pandang Al-Qur’an - Alhamida, Alhamida; Kusuma, Atik Devi; Hasanah, Dinda Putri; Majah, Ibnu; Wismanto, Wismanto (STAI Denpasar Bali, 2024)
The method is one of the ways in the world of educators in the learning process so that the participants can achieve learning goals. Many verses of the Qur'an and the Hadist explain about the use of methods in education. In Islamic religious people who learn to understand will have knowledge that will be useful for the life of life in the world and the presence in the hereafter. The purpose of this education is to reveal the behavior or the mind but it should be based on the guidelines of the Qur'an and the Hadits and Islamic education should be based on the Quran and the Hadist where in Islam there is a source of law. The method used in this study is qualitative using the library and resource approaches that the main data of this research is a reading material from books, magazines, articles, journals and the Hadist Books. The results of this study show that there are several ways that the teacher has to teach in a student to achieve a purpose in line with the guidance of the Quran and the Sunnah and can be known that the education method is one of the key components in learning.